Bimbingan Spiritual Bagi Jemaah Santri Luwung - Arnis Rachmadhani (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
A religious group called Pasujudan Santri Luwung Padepokan Bumi Arum in Sragen district has created problems in the surrounding Muslim community. This is because their teaching was considered as deviance from Islamic teaching generally. Apart from this polemic, the existence of new religious group has attracted some people to follow and enroll in this Santri Luwung group. This is a qualitative research focusing on the phenomena of religious life especially new religious group or it is named as religious movement. Data was collected through observation, interviews, and documentary study. Data was analyzed using interactive analysis. This study depicts that the teaching of Padepokan Santri Luwung is an acquaintance between Islam and Kejawen (Javanese teaching). This can be recognized as a new religious movement. It can give social nuance to the follower of Santri Luwung; they get the teaching from various activities such as dakwah, social, education, health program, economy and art program.